True acrosome reaction in buffalo (Bubalus bubalis) spermatozoa - Kaur, Jagjit; Sidhu, K S; Guraya, S S (The Indian Journal of Animal Sciences, 2012)
True acrosome reaction in buffalo spermatozoa using TALP medium, was studied. This reaction was estimated using 'dual-staining procedure. Sperm percent motility, true and false acrosome reactions were evaluated each hour during 8 hr of incubation. The percent motility decreased progressively with increasing time of incubation. The initiation of true acrosome reaction was at 3hr of the incubation and progressively increased with increasing time of incubation with maximum (60%) at 8 hr. The 3 stages of aerosome reaction such as aerosome swelling, vesiculation and shedding were observed. The biological significance of the true and false aerosome reaction has been discussed.